2009
DOI: 10.1007/s10640-009-9307-3
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Validity of Revealed and Stated Recreation Behavior with Quality Change: A Comparison of Multiple and Single Site Demands

Abstract: Recreation demand, Travel cost method, Convergent validity, Revealed preference, Stated preference,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…In the model, travel cost for accessing the site is interpreted as the price, and the number of trips taken in the season is the quantity demanded at that price. 2 The main strength of the travel cost method is that it is based on actual choices (revealed preference) as a recreator considers the benefits and costs of participation and experience along with the consequences of their actions (Whitehead et al, 2009). However, a primary weakness of the travel cost method is that it relies on historical data so analyzing site quality changes, such as changes in the size of a site or improved site access, might not be feasible because individuals may not be able to form preferences due to lack of an actual experience.…”
Section: Introductionmentioning
confidence: 99%
“…In the model, travel cost for accessing the site is interpreted as the price, and the number of trips taken in the season is the quantity demanded at that price. 2 The main strength of the travel cost method is that it is based on actual choices (revealed preference) as a recreator considers the benefits and costs of participation and experience along with the consequences of their actions (Whitehead et al, 2009). However, a primary weakness of the travel cost method is that it relies on historical data so analyzing site quality changes, such as changes in the size of a site or improved site access, might not be feasible because individuals may not be able to form preferences due to lack of an actual experience.…”
Section: Introductionmentioning
confidence: 99%
“…Landry & Liu (2011) extend this analysis to several other parametric models and find that the beach width scenario increases recreation trips in three of four models. Whitehead et al (2010) examine beach recreation behavior using multiple-site, revealed preference data, exploiting the existing variation in beach width in the choice set of North Carolina beaches. The value of a 100-foot increase in beach width across all sites in the study area is estimated.…”
Section: Beach Recreationmentioning
confidence: 99%
“…Economic values for preventing erosion have been estimated at $7.88 to $14.81 per household, per trip for Delaware beaches (Parsons, Massey, and Tomasi 2000), and $46.01 to $78.09 per household, per year for all beaches in Virginia, Maryland, and Delaware (von Haefen, Phaneuf, and Parsons 2004). Focusing on southern North Carolina beaches, Whitehead, et al (2010) estimate $3.57 per individual, per trip, and $8.32 to $17.84 per household, per year for a 100-foot increase in beach width. Parsons, Massey, and Tomasi (2000) and Whitehead et al (2010) find evidence that beach length has positive influence on site choice, indicating a preference for longer beaches.…”
Section: Beach Visitorsmentioning
confidence: 99%
“…Focusing on southern North Carolina beaches, Whitehead, et al (2010) estimate $3.57 per individual, per trip, and $8.32 to $17.84 per household, per year for a 100-foot increase in beach width. Parsons, Massey, and Tomasi (2000) and Whitehead et al (2010) find evidence that beach length has positive influence on site choice, indicating a preference for longer beaches.…”
Section: Beach Visitorsmentioning
confidence: 99%